2008
DOI: 10.3732/ajb.0800034
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for “diminishing returns” from the scaling of stem diameter and specific leaf area

Abstract: Research indicates that increases in total leaf area (A(T)) may fail to keep pace with increases in total leaf mass (M(L)) across plants differing in size (e.g., as measured by stem diameter, D). This "diminishing returns" hypothesis predicts that the scaling exponent for A(T) vs. M(L) will be less than one and that the exponent for specific leaf mass (i.e., A(T) / M(L)) vs. D will be negative. These predictions were examined using data from 46 plants ranging between 0.125 cm ≤ D ≤ 0.485 m across 25 woody dico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 45 publications
(80 reference statements)
4
44
2
Order By: Relevance
“…3a-b and (4)) made it possible to predict accurately A t , B t , and SLA t from DBH. As reported in two recently published studies (Holdaway et al, 2008;Niklas and Cobb, 2008), we found that A t increased non-isometrically with B t : for increasing tree size, A t increased more slowly than B t (b A < b B ), thus explaining the decreases in SLA t with increasing DBH (a < 1, and b SLA < 0). Our mean a value (0.91; Table 1) was similar to the mean value (0.90) found by Holdaway et al (2008) for several Nothofagus solandri stands in New Zealand.…”
Section: Within-stand Variations In Sla Tsupporting
confidence: 67%
See 1 more Smart Citation
“…3a-b and (4)) made it possible to predict accurately A t , B t , and SLA t from DBH. As reported in two recently published studies (Holdaway et al, 2008;Niklas and Cobb, 2008), we found that A t increased non-isometrically with B t : for increasing tree size, A t increased more slowly than B t (b A < b B ), thus explaining the decreases in SLA t with increasing DBH (a < 1, and b SLA < 0). Our mean a value (0.91; Table 1) was similar to the mean value (0.90) found by Holdaway et al (2008) for several Nothofagus solandri stands in New Zealand.…”
Section: Within-stand Variations In Sla Tsupporting
confidence: 67%
“…Similar tree size related differences in SLA have been reported for other tree species (e.g., Niinemets, 1997;Holdaway et al, 2008;Niklas and Cobb, 2008), but it is still unclear if these differences are mostly driven by ontogenic changes (e.g., Day et al, 2001), differences in light-environment (e.g., White and Scott, 2006), or increased water limitation with tree size (e.g., Woodruff et al, 2004;Cavaleri et al, submitted for publication).…”
Section: Within-stand Variations In Sla Tmentioning
confidence: 65%
“…The reduction of leaf area during water deficit is typical for plants from arid stands. Several authors (Reich et al, 2003, Wright et al, 2004Niclas & Cobb, 2008) have confirmed the narrow relationship between leaf structure and function. Our comparison of the leaf area ratio to dry weight of the leaves (SLA) of the analysed species confirmed the interspecific differences (Table 1).…”
Section: The Influence Of Water Stress On the Production Of Leaf Dry mentioning
confidence: 87%
“…Oven dry leaf masses were first transformed to the ¾ power before this standardization step. This transformation incorporates a concept of diminishing returns whereby leaf area increases ever more slowly as leaf mass increases, i.e., at a power of ¾ of leaf mass (Niklas & Cobb, 2008). This transformation was not done originally with the 2007 leaf collection (Sheppard et al, 2009a), but it has since been done on that data set in addition to the data from 2008-2010.…”
Section: Quantitative Analysismentioning
confidence: 99%